Optimization of Government Investment in Capital Accumulation For The Period 2004-2020 Iraqi Economy - Jabbar Hussein, Hashim (UMSurabaya Publishing, 2025)
This article aims to study the optimality of government investment in capital accumulation in the Iraqi economy, focusing on the impact of taxes and non-oil revenues. The research problem lies in the fact that government spending, despite its increase after 2004, did not contribute sufficiently to raising the efficiency of the Iraqi economy and achieving social justice. The researcher used a number of statistical programs, namely (Microsoft Excel vs. 16, SPSS VS. 25, Eviews Vs. 12, Smart Pls 4). The results showed that increasing taxes negatively affects investment decisions, which hinders capital accumulation and reduces the efficiency of government spending, which requires improving investment efficiency and directing resources towards productive sectors such as agriculture and industry. The research came out with a number of recommendations, the most important of which is re-evaluating the tax system to reduce tax rates and enhance tax exemptions for investors, which contributes to attracting investment and achieving sustainable development. Balanced tax policies should also be formulated to ensure the achievement of government revenues without a significant negative impact on capital accumulation